2017
DOI: 10.1159/000477170
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metabolic Syndrome and Serum Nerve Growth Factor Levels in Women with Overactive Bladder

Abstract: Objective: This study aimed to determine the association between overactive bladder (OAB), metabolic syndrome (MetS) and serum nerve growth factors (NGF). Study Design: Serum samples from a group of 90 women that included patients with OAB (group 1), patients with both OAB and MetS (group 2) and healthy women without OAB and MetS (group 3). Each group included 30 patients. Serum levels of NGF were compared among the groups. Results: When the groups were compared with respect to NGF levels, group 2 was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…23 The articles were published from 2012 19,22 to 2018. 18 Enrolled subjects were 2600 in the primary studies [18][19][20][21][22] and 108 367 in the review. 17 In the studies examined, the following types of subjects were present: 633 with MetS and 1227 without MetS, in Zacche et al 23 ; 1011 with OAB and 535 without OAB, in Ohgaki et al 19 In the review of Bunn et al, the age range is from 20 to 79 years 17 ; in primary studies from 25 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The articles were published from 2012 19,22 to 2018. 18 Enrolled subjects were 2600 in the primary studies [18][19][20][21][22] and 108 367 in the review. 17 In the studies examined, the following types of subjects were present: 633 with MetS and 1227 without MetS, in Zacche et al 23 ; 1011 with OAB and 535 without OAB, in Ohgaki et al 19 In the review of Bunn et al, the age range is from 20 to 79 years 17 ; in primary studies from 25 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies included in the review, the following evaluation criteria were used for the MetS: NCEP ATP III 19,20 ; IDF [18][19][20] ; Japan Society for the Study of Obesity 18 ; American Heart Association definition of MetS. 21 In Bunn's review, the criteria for diagnosing MetS were: WC and levels of triglycerides, high-density lipoprotein cholesterol, blood pressure and fasting glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Investigators found that individuals with OAB and metabolic syndrome had higher serum NGF compared to those with OAB without metabolic syndrome and also compared to healthy controls. 18 However, the relationships between systemic NGF and urinary NGF are not entirely clear. In a prior study performed with the Promega ELISA kit Liu et al demonstrated that serum and urine NGF are highly correlated and are both elevated in patients with OAB compared to controls.…”
Section: Biomarkers Of Overactive Bladdermentioning
confidence: 99%
“…The reduced afferent input to the central nervous system may explain the observed sensory effects seen in clinical practice after administration of antimuscarinic agents. [34] The mode of action of β3 agonist is slightly different in comparing to antimuscarinics. During the filling phase of the bladder, β3 agonist causes relaxation of detrusor in terms of basal tone.…”
Section: Medication In Oabmentioning
confidence: 99%
“…In their research they found serum NGF levels were elevated in patients with both metabolic syndrome and OAB compared to the levels in the healthy controls. [34] In the future, we should combine the design of the patient tailored treatment algorithm as described by Peyronnet [22] with fundamental research as performed by Cartwright et al in UUI separately. [35] Ideally, we could develop a specific responder model based on the patients etiology of OAB and the best fitting treatment modality for this subtype of OAB in terms of efficacy, safety and usability for this specific OAB patient population based on detected biomarker profiles.…”
Section: Future Perspectivesmentioning
confidence: 99%